Catastrophic disassembly of actin filaments via Mical-mediated oxidation - Elena E. Grintsevich (Nature Portfolio, 2017)
MICAL Redox enzymes post-translationally modify F-actin to promote its cellular destabilization. Here, the authors present a 3.9Å cryoEM structure of Mical-oxidized F-actin, showing its nucleotide-state dependent dynamic instability and susceptibility to cofilin-induced severing in the presence of inorganic phosphate.